Religious Moderation amid Globalization: The Challenges of Taṭarruf, Takfīr, and Taʻāṣub - Armita, Pipin; Yusuf, Maulana; Maulana, Muhammad Zein (Al-Wasatiyah: Journal of Religious Moderation, 2025)
The phenomenon of globalization has had a profound impact on how societies conceptualize and engage with religious practices. In the context of globalization, challenges such as taṭarruf (extremism), takfīr (excommunication), and taʻāṣub (fanaticism) have underscored the imperative for the promotion of religious moderation. The objective of this study is to examine the notion of religious moderation as a potential remedy for extremism, excommunication, and fanaticism. Employing a qualitative research method and a library-based approach, the study reveals that religious moderation is essential for harmonizing religious principles with the challenges posed by global change. It is also positioned as an effective approach to countering religious extremism, reducing excommunication, and mitigating fanaticism that threatens social harmony. However, this study also identifies challenges in implementing religious moderation, particularly in addressing radicalism driven by globalization. This study addresses a significant research gap in the field of religious moderation by underscoring the absence of effective strategies for integrating moderation values into educational and social policies. The practical implications of this research underscore the necessity of fortifying the role of educational institutions, media outlets, and government policies in methodically and sustainably promoting religious moderation.